Studies on nutrient management and seed rate on growth and herbage yield of fenugreek (Trigonella corniculata L.) cv. Kasuri in Rajasthan - L Reager, N S Deora, Jitendra Singh, M (Journal of Spices and Aromatic Crops, 2009)
A field experiment was conducted at Bikaner and Jalore (Rajasthan) to study the effect offertilizer and vermicompost and four levels of seed rate on growth attributes of fenugreek(Trigonella corniculata) cv. Kasuri. The results showed that application of fertilizer (20 kg N+ 4 kg P2O5 ha-1) increased plant height, number of branches plant-1, dry matter accumulationand number of root nodules, over control. Vermicompost @ 4 t ha-1 significantly improvedgrowth attributes. Growth parameters such as plant height, herbage yield and dry weightof leaves, increased significantly with increasing levels of seed rate up to 7.5 kg ha-1, whereas,nodules plant-1, fresh root weight and number of branches plant-1 decreased significantly upto 7.5 kg ha-1.